Encapsulated thyme (Thymus vulgaris) essential oil used as a natural preservative in bakery product. (June 2017) - Gonçalves, Nathalia Dias; Pena, Fabíola de Lima; Sartoratto, Adilson; Derlamelina, Camila; Duarte, Marta Cristina Teixeira; Antunes, Adriane Elisabete Costa; Prata, Ana Silvia
Abstract: The objective of this work was to design a particle using thyme ( Thymus vulgaris ) essential oil through complex coacervation. In vitro activity against bacteria and molds of free oil as well as the encapsulated oil was verified and then in situ assay was done. The free thyme oil presented high in vitro activity, with values below 0.50 mg/mL for almost all the microorganisms tested. Also, MIC values for the encapsulated oil was lower than for the free oil, probably due to the protective micro-environment promoted by the particle wall. The microparticles applied to cakes samples conferred protection against the volatilization of the encapsulated oil and promoted a minimum shelf life of 30 days without the use of synthetic preservatives. Graphical abstract: Highlights: Thyme oil was efficient against bacteria and molds. Microparticles were ten times more effective than the free oil in the " in vitro " test. Shelf life of the cakes with added microparticles was improved (> 30 days).